Simultaneous double pulse enhanced laser induced breakdown spectroscopic detection of trace heavy metals in herbs - Rizvi, Syed Zuhaib Haider (2015)
Laser Induced Breakdown Spectroscopy (LIBS) is a versatile technique. It has enormous potential for in-situ elemental analysis of virtually any kind of material. Undesired fluctuations in analytical conditions seriously influence its quantitative measurements. Double Simultaneous Pulse (DSP) configuration is introduced in this work that can potentially minimize the influence of error factors and improve repeatability as well as detection limit. Its performance is compared with conventional Single Pulse (SP) LIBS configuration in a series of experiments performed under controlled environments of air and argon. Herbal samples Ficus Deltoidea, Phaleria Macrocarpa and Strobilanthes Crispus are utilized as investigative materials. Nd:YAG laser (1064 nm, 6 ns, 544 mJ) and Ocean Optics HR4000 spectrometer are employed for laser induced breakdown spectroscopic studies. Mg, Ca, Pb and Cu are quantified in samples through both configurations of LIBS. Better line profiles, emission intensities, signal-to-noise ratios (SNRs) and signal-to-background ratios (SBRs) are observed with DSP configuration. Electron density and plasma temperatures obtained from DSP configuration are slightly higher than those obtained with SP configuration. Comparatively, DSP configuration performs better in the estimation of heavy metal concentrations. Linear correlations of the calibration plots, limits of detection (LODs), relative standard deviation (RSD) and Errors of Prediction are generally improved. Minimum LODs obtained for Pb, Cu, Mg and Ca are 38.63 μg/g, 47.75 μg/g, 8.92 μg/g and 8.72 μg/g respectively. Minimum values of root mean square error of prediction (RMSEP) in the measurements, as yielded from SP and DSP configurations, are 83.13 μg/g and 43.13 μg/g respectively. Smaller errors and better repeatability are found as special traits of argon while smaller LOD is that of air environment. In this study DSP outperforms SP configuration at several fronts in both environments. It concludes that DSP can be a better alternative configuration of LIBS for quantification of heavy metals in herbal plants.